Business strategies of snack food product export performance: A structural equation model analysis - Sawitree Boonnarakorn; Samart Deebhijarn; Woranat Sangmanee (My University, 2023)
Over the past several years the COVID-19 pandemic has devasted Thailand’s economy while simultaneously destroying the ability of numerous snack food enterprises to sell their home-grown products domestically and to export to the broader international community. Therefore, the purpose of the research was to investigate which factors affected the export performance (XPE) of Thai One Tambon One Product (OTOP) entrepreneur snack food products. From a list of OTOP export producers, the authors used systematic random sampling across six Thai regions to select the study’s 311 export entrepreneurs. The structural equation model (SEM) analysis used LISREL 9.1 to determine the validity of the causal model and the variable interrelationships and how they affected OTOP snack food XPE. The SEM results revealed that innovative products (IPT), innovative processes (IPS), packaging design (PAD), the marketing mix strategy (MMS), and product quality (PDQ) all positively influenced XPE. Also, the total effect values for MMS, PAD, PDQ, IPT, and IPS, were 0.27, 0.22, 0.21, 0.15, and 0.05, respectively. Nine of the eleven hypotheses examined were supported, with PAD being shown to strongly influence MMS. This paper makes a significant contribution to the global discussion concerning rural poverty reduction, rural employment, and entrepreneurial handicraft export performance.
Keywords: LISREL; Export performance; Innovation and Socioeconomic Development